2015
DOI: 10.3233/jpi-2012-0327
|View full text |Cite
|
Sign up to set email alerts
|

Leuconostoc sepsis in a previously healthy neonate

Abstract: Leuconostoc sepsis is more commonly described in extreme of ages with risk factors of infection such as prematurity, individuals with gastrointestinal processes, needing parenteral nutrition, carrying central venous catheters, prolonged antibiotic therapy and immunosuppression. We report the case of a previously healthy 22 days old female with no risk factors that developed Leuconostoc sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Moreover, we also found that the 3 ZOTUs belonging to Bifidobacterium panos were strongly correlated with multiple colonizing genera in colon tissue, such as Leuconostoc , Akkermansia , Mesomycoplasma , Aquirufa , and Polynucleobacter . Among them, the genera Leuconostoc , Akkermansia , and Polynucleobacter have been reported to play critical roles in the development of sepsis or bacteremia ( Patel et al., 2012 ; Pavon-Delgado et al., 2015 ; Morowitz et al., 2017 ; Adelman et al., 2020 ; Wang et al., 2021 ). These results suggest that the migration of Bifidobacterium panos to colon tissue in late sepsis may be an important event in the progression of sepsis, which is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we also found that the 3 ZOTUs belonging to Bifidobacterium panos were strongly correlated with multiple colonizing genera in colon tissue, such as Leuconostoc , Akkermansia , Mesomycoplasma , Aquirufa , and Polynucleobacter . Among them, the genera Leuconostoc , Akkermansia , and Polynucleobacter have been reported to play critical roles in the development of sepsis or bacteremia ( Patel et al., 2012 ; Pavon-Delgado et al., 2015 ; Morowitz et al., 2017 ; Adelman et al., 2020 ; Wang et al., 2021 ). These results suggest that the migration of Bifidobacterium panos to colon tissue in late sepsis may be an important event in the progression of sepsis, which is worthy of further study.…”
Section: Discussionmentioning
confidence: 99%